2022
DOI: 10.1016/j.envres.2021.111877
|View full text |Cite
|
Sign up to set email alerts
|

Effect of selected wastewater characteristics on estimation of SARS-CoV-2 viral load in wastewater

Abstract: Wastewater-based epidemiology has been used as a tool for surveillance of COVID-19 infections. This approach is dependent on the detection and quantification of SARS-CoV-2 RNA in untreated/raw wastewater. However, the quantification of the viral RNA could be influenced by the physico-chemical properties of the wastewater. This study presents the first use of Adaptive Neuro-Fuzzy Inference System (ANFIS) to determine the potential impact of physico-chemical characteristics of wastewater on the detection and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 46 publications
0
28
0
Order By: Relevance
“…For Edmonton and Toronto, SARS-CoV-2RNA was extracted from the solid fraction of influent samples. The solid concentration can be affected by the influent flow volume and environmental factors such as precipitation and sedimentation Bertels et al, 2022 , Amoah et al, 2022 . Hence, for these locations, SARS-CoV-2concentrations in wastewater was normalized by the total solid suspension (TSS) measured on the sampling day at the treatment plant.…”
Section: Methodsmentioning
confidence: 99%
“…For Edmonton and Toronto, SARS-CoV-2RNA was extracted from the solid fraction of influent samples. The solid concentration can be affected by the influent flow volume and environmental factors such as precipitation and sedimentation Bertels et al, 2022 , Amoah et al, 2022 . Hence, for these locations, SARS-CoV-2concentrations in wastewater was normalized by the total solid suspension (TSS) measured on the sampling day at the treatment plant.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the lack of clinical viral shedding data from vaccinated (single or multiple doses) and unvaccinated individuals, patients with varied severity of symptoms, as well as across SARS-CoV-2 variants also hampers a wide range of WBE endeavours, including calculating the incidence of infection in sewersheds, estimating the effective reproduction number of SARS-CoV-2 in a population ( Huisman et al, 2021 ) and inferring transmission fitness of VOCs from wastewater data ( Caduff et al, 2021 ). On the other hand, viral concentrations in wastewater are impacted by the transient flow rates, water pH, viral degradation and detention in wastewater lines ( Amoah et al, 2022 ; Khan et al, 2021 ; Simpson et al, 2021 ), further undermining WBS data applications.…”
Section: Challenges and Future Developments Of Wastewater Surveillancementioning
confidence: 99%
“…Previous studies have reported that SARS-CoV-2 can mostly survive when the pH of the HWW is between 6 and 8 ( Amoah et al, 2022 ; Varbanov et al, 2021 ). La Rosa et al (2020) have reported SARS-CoV-2 is highly sensitive to alkaline water and can be inactivated in chlorinated water ( La Rosa et al, 2020 ).…”
Section: Hospital Wastewater and Biomedical Waste Management In The Context Of Covid-19mentioning
confidence: 99%